2000
DOI: 10.1148/radiology.217.2.r00nv36377
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Gliomas: MR Imaging Spectrum of Radiation Therapy- and Chemotherapy-induced Necrosis of the Brain after Treatment

Abstract: The frequent diagnostic dilemma of recurrent neoplasm versus radiation necrosis is addressed in this study through a description of the varying spatial and temporal patterns of radiation necrosis at MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
383
1
17

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(409 citation statements)
references
References 24 publications
(17 reference statements)
4
383
1
17
Order By: Relevance
“…Conventional MR imaging features and MR spectroscopic imaging have been used to differentiate radiation necrosis from recurrent tumors with mixed success. 27,28 Various forms of metabolic imaging techniques have been used in the past with limited results. FDG-PET, 29 which is based on tumor glucose metabolism, has shown variable sensitivity and specificity in differentiating recurrent tumors from radiation necrosis and also has limited spatial resolution.…”
Section: Role Of Pct In Differentiating Recurrent Tumor From Radiatiomentioning
confidence: 99%
“…Conventional MR imaging features and MR spectroscopic imaging have been used to differentiate radiation necrosis from recurrent tumors with mixed success. 27,28 Various forms of metabolic imaging techniques have been used in the past with limited results. FDG-PET, 29 which is based on tumor glucose metabolism, has shown variable sensitivity and specificity in differentiating recurrent tumors from radiation necrosis and also has limited spatial resolution.…”
Section: Role Of Pct In Differentiating Recurrent Tumor From Radiatiomentioning
confidence: 99%
“…Therefore, MRI cannot be used postoperatively after day 3 and for several weeks because the surgical damage of the BBB, with subsequent leakage of contrast media, leads to a false-positive indicator of the presence of residual or recurrent tumor. Moreover, conventional MRI techniques usually fail to detect early effects of radio-and chemotherapy because individual treatment effects are only visible after more than 12 months, [133][134][135] with a substantial interobserver variability in the assessment of treatment response. 136 Especially after the application of biologically active agents (gene therapy vectors, toxins), the value of conventional MRI to detect therapy-specific changes of tumor viability is limited 137 as reviewed previously.…”
Section: Imaging For Determination Of Treatment Effect Tumor Progresmentioning
confidence: 99%
“…The specifications of cut point for differentiation between tumor progression and radiation necrosis was the topic of numerous studies. [6,7,8,9,10] Sugahara et al in the prospective study with 20 patients concluded that normalized relative cerebral blood volume (rCBV) higher than 2.6 and lower than 0.6 suggests tumor recurrence or non-neoplastic contrast enhancing tissue, respectively. [11] Hein et al in retrospective study of 18 patients analysed the value of DWI in the follow up of treated high-grade gliomas.…”
Section: Discussionmentioning
confidence: 99%